Lesions of the buccal mucosa in elderly. A study performed in five family doctor´s office of health area III in Cienfuegos city. - Beatriz García Alpízar; Arturo Guerra Alfonso; Mikhail Benet Rodríguez (Medisur)
Fundament: Bucal lesions in aged persons are very frequent and are not the same in many countries and regions. To know about them is of great importance for we can plan preventive activities and medical services for their attention Objective: To describe the more frequent intraoral mucous lesions in individuals with 60 years old and more. Methods: Descriptive study with a sample of 270 aged persons (both sexes), obtained through simple random sample out of a universe of 1014 individuals with 60 years old and more, from Area III in Cienfuegos. Detailed physical examination was applied to all the studied patients as well as a questionnaire where data of interest were engulfed. Results: From all studied cases, the 26.7% presented some type of bucal lesion, predominantly in women (17.8%). The more frequent lesions were: sub prosthesis stomatitis (10%), leukoplasia (6.2%), and fissuratum epulis (4.4%). The more frequent anatomic localizations of these lesions were: the palatum durum with 27 cases of sub prosthesis stomatitis, the alveolar sulcus with 11 fissuratum epulis, and the jugal mucosa with 4 cases of candidiasis and 7 leukoplasias. Conclusions: A high percentage of this geriatric population presented some type of bucal mucosa lesions, women were the most affected, lesions of prosthetic origin were predominant, as well as pre malignant lesions. The predominant localizations of the lesions were the palatum durum, the alveolar sulcus, and the jugal mucosa.